Pengembangan Kelembagaan dalam Rangka Peningkatan Manajemen Produk Ikan Teri di Desa Saramaake, Halmahera Timur, Maluku Utara - Ujang Sehabudin; Bahroin Tampubolon; . Sulistiono; . Sudarmanto; . Arisyono; Resna Handayani (Institut Pertanian Bogor, 2019)
One of the villages in East Halmahera Regency known as center of anchovy catch production area is Saramaake Village. The fishery community empowerment activities were carried out for 6 months from June to December 2017, aimed at developing institutions in order to improve production management and added value of anchovy. Methods used were training and mentoring conducted by experts and field mentors. The scope of activities includes institutional development, training, and mentoring. Institutional development was begun by lift-net fishermen and fish processing group establishment, developing business group (KUB-Indonesian) and cooperative. The data used was consisted of primary data (based on interview, observation, and mentoring) and secondary data (village profile and fish production). Based on activities carried out, the institution that has been built since 2016 has been upgraded from fishermen and fish processors groups, to business group (KUB), then developed into cooperatives in 2017. The Akesalaka Monge Bahari producer cooperative has obtained a legal entity No.006389/BH/M.KUKM.2/XI/2017. The cooperative was able to implement a better togetherness work to produce fish processing, and wider market development. Through this institutional development, fishermen and marine processors can be better to manage their business independently and be able to increase the bargaining position in the marketing of anchovy and other processed marine products.